Structural degradation of puddle irons and steels from old riveted metallic bridges - Raposo, Patrícia (2017)
In repairing and strengthening operations of ancient riveted steel bridges is important to estimate and assess the structural degradation of the old metals in order to guaranty the structural safety. Long-time operated metallic materials (mild, rimmed low carbon steels < 0.1% C, puddle irons) subjected to cyclic loading show tendency to the microstructural degradation processes. In this paper, the study of the structural degradation of puddle irons and steels from old metallic bridges with long-term operation is proposed.